Long non-coding RNA linc00152 acting as a promising oncogene in cancer progression - Danbi Seo; Dain Kim; Wanyeon Kim (Genomics & Informatics)
The incidence and mortality rate of cancer continues to gradually increase, although considerable research effort has been directed at elucidating the molecular mechanisms underlying biomarkers responsible for tumorigenesis. Accumulated evidence indicates that the long non-coding RNAs (lncRNAs), which are transcribed but not translated into functional proteins, contribute to cancer development. Recently, linc00152 (an lncRNA) was identified as a potent oncogene in various cancer types, and shown to be involved in cancer cell proliferation, invasiveness, and motility by sponging tumor-suppressive microRNAs acting as a competing endogenous RNA, binding to gene promoters acting as a transcriptional regulator, and binding to functional proteins. In this review, we focus on the oncogenic role of linc00152 in tumorigenesis and provided an overview of recent clinical studies on the effects of linc00152 expression in human cancers.